Ancient marine sediment DNA reveals diatom transition in Antarctica - Armbrecht, Linda; Weber, Michael E.; Raymo, Maureen E.; Fogwill, Chris; et al. (Springer Nature, 2022)
Antarctica is one of the most vulnerable regions to climate change on Earth and studying the past and present responses of this polar marine ecosystem to environmental change is a matter of urgency. Sedimentary ancient DNA (sedaDNA) analysis can provide such insights into past ecosystem-wide changes. Here we present authenticated (through extensive contamination control and sedaDNA damage analysis) metagenomic marine eukaryote sedaDNA from the Scotia Sea region acquired during IODP Expedition 382. We also provide a marine eukaryote sedaDNA record of ~1 Mio. years and diatom and chlorophyte sedaDNA dating back to ~540 ka (using taxonomic marker genes SSU, LSU, psbO). We find evidence of warm phases being associated with high relative diatom abundance, and a marked transition from diatoms comprising <10% of all eukaryotes prior to ~14.5 ka, to ~50% after this time, i.e., following Meltwater Pulse 1A, alongside a composition change from sea-ice to open-ocean species. Our study demonstrates that sedaDNA tools can be expanded to hundreds of thousands of years, opening the pathway to the study of ecosystem-wide marine shifts and paleo-productivity phases throughout multiple glacial-interglacial cycles.
Keywords: Biodiversity; Marine biology; Metagenomics; Palaeoceanography; Palaeoecology